Morphological indicators of nutria blood during trichurosic invasion - E. Mykhailiutenko, E. (Scientific Progress & Innovations, 2024)
It is generally accepted that the immune system plays an important role in the pathogenesis of almost any disease. Circulating phagocytes (neutrophils, monocytes) are the first to be involved in the development of an inflammatory reaction. The state of erythrocytopoiesis is a unique mechanism that occupies a dominant position in ensuring tissue respiration and stability of metabolic processes in the body. Laboratory blood tests are a primary indicator of changes in the body. On the territory of Ukraine, insufficient attention is paid to the study of morphological indicators in infested nutrias. Although based on research and analysis of publications, scientists claim that changes in erythrocytopoiesis indicate a pathological condition of animals. Therefore, the purpose of our work was to determine the effect of trichurises on the morphological indicators of sick semi-aquatic rodents. The work was carried out in the conditions of the farm "Dokuchaievskyi myslyvets" of the Poltava region. An experimental group of 8-month-old animals was formed, as well as a control group (eight heads each). Morphological indicators were studied according to generally accepted methods. The article summarizes the results of an experiment on the effect of trichurises on the composition of the blood of infested nutrias. It was found that parasitism in semi-aquatic rodents of the species Trichuris myocastoris causes changes in the general blood analysis: a decrease in the hemoglobin content by 15.05 %, and the number of erythrocytes by 19.37 %. A decrease in these indicators confirms the occurrence of anemia. At the same time, a decrease in leukocytes by 6.64 % may indicate a chronic course of the disease. As a result of the conducted morphological study of the uniform elements of nutria blood with a differential count of the leukocyte formula, a redistribution of the population composition of circulating leukocytes was established, caused by the maintenance / presence of the inflammatory process. A significant increase in the number of monocytes by 25.77 % was diagnosed. Therefore, the composition of the blood mutually determines the nature of the processes taking place in the nutria's body, and reflects the effect of trichurises perceived by it. The results of morphological studies of the blood of infested nutrias indicate significant changes in their body and confirm the mediated effect of the helminth.